Flavonoid Glycosides from Tribulus terrestrisL.orientalis: Flavonoids from Tribulus terrestrisL - Marzieh Matin Yekta,; Seyed Hamid Reza Alavi,; Yousef Ajani,; Reza Hadjiaghaee, (Iranian Journal of Pharmaceutical Sciences, 2008)
Tribulus terrestrisL. var. orientalis(Kerner) G. Beck is widely used in the traditional medicine of many countries. Several flavonoides are identified from the plant material. Aerial parts which collected from northeast of Iran are used in this study. Three flavonoid glycosides were isolated and characterized. The flovonoids were found to be based on quercetin and kaempferol. Flavonoid glycosides whichs eparated were consisted of quercetin 3-O-glycoside, quercetin 3-O-rutinoside and kaempferol 3-O-glycoside. The latest one was a new for the plant.